A campanha presidencial de 1950 a partir da imprensa passo-fundense: Diário da Manhã e O Nacional - Adam, Caroline (2024)
Historical research can be done in different ways, focusing on sources varied, both in formats, perspectives and methodologies. That said, would it be possible study the Brazilian presidential campaign of 1950 from different sources and perceptions. However, considering the press is especially rich in informative content and also ideological, as it is capable of presenting perspectives on society at the time, we will use it as a source for this research. Thus, we will seek to analyze the electoral campaign process of October 3, 1950 from the Passo Fundo press, more specifically dealing with periodicals Diário da Manhã and O Nacional, safeguarded respectively at the Historical Institute of Passo Fundo (IHPF) and in the Regional Historical Archive (AHR), at the University of Passo Fund (UPF). In other words, in this way we will be studying the traditional objects of History Politics, but with a new source, the press. Therefore, the objective of this research is to explore the impact of the campaign Brazilian presidential election of 1950, in the city of Passo Fundo, understanding how elections were portrayed in the local press. Also seeking to reveal the relationship between the periodicals Diário da Manhã and O Nacional with the parties and candidates they supported and/or made opposition, also aiming to cover the political motivations of this position. Then, from How this event of great national relevance had repercussions on the local press in Passo Bottom?